2019
DOI: 10.25019/mdke/7.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Banking Services in the Knowledge Economy

Abstract: In this paper, we have covered many of the roles that banks play in the financial system. Banks act as delegated monitors that ensure that economic agents allocate their resources effectively, thus leading to the sustainable development of entrepreneurship. Moreover, they also play an important role in sharing risks in the economy and protecting economic agents against market fluctuations through various means such as financial derivatives. These are the positive aspects of the roles of banks, but it should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Previous research has confirmed that habit is one of the key predictors of customer intention and behaviour when adopting mobile or internet banking services. Habitual behaviour in using a technology plays a big part in facilitating consumers' actual behaviour towards mobile banking (Farzin et al, 2021;Alalwan et al, 2015;Hadad, 2013;Venkatesh et al, 2012) In line with these findings (Anggraeni et al, 2021), also found that habit is a goaldirected automatic response, that leads to high predictive power. Taking this into consideration, habit is found to be the main antecedent of usage.…”
Section: The Relationship Between Habit and Intention To Adopt Digita...mentioning
confidence: 81%
See 1 more Smart Citation
“…Previous research has confirmed that habit is one of the key predictors of customer intention and behaviour when adopting mobile or internet banking services. Habitual behaviour in using a technology plays a big part in facilitating consumers' actual behaviour towards mobile banking (Farzin et al, 2021;Alalwan et al, 2015;Hadad, 2013;Venkatesh et al, 2012) In line with these findings (Anggraeni et al, 2021), also found that habit is a goaldirected automatic response, that leads to high predictive power. Taking this into consideration, habit is found to be the main antecedent of usage.…”
Section: The Relationship Between Habit and Intention To Adopt Digita...mentioning
confidence: 81%
“…Likewise, research conducted by (Farzin et al, 2021;Alalwan et al, 2015;Hadad, 2013;Venkatesh et al, 2012) discovered that habitual behaviour in using technology plays a big part in facilitating consumers' actual intention to adopt mobile banking services.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is also important to mention that The UN Inter-Agency Task Force on Social and Solidarity Economy (UN Inter-Agency Task Force on Social and Solidarity Economy, 2014) noted the importance of the Social and Solidarity Economy, indicating that it could play a key role in achieving the 2030 Agenda and the 17 Sustainable Development Goals. Social and Solidarity Economy, as an alternative development model, holds considerable promise for addressing the economic, social, and environmental integrated approaches to sustainable development (Barna, 2020). At the beginning of 2022, OECD, together with European Commission launched the report "Policy brief on making the most of the social economy's can contribute to the circular economy", detailing how specific assets of the social economy can contribute to the actual circular economy challenges: the social economy has a demonstrated experience in developing circular activities, the social economy makes the transition to the circular economy more inclusive, the social economy can inspire business models and practices based on collaboration at the local level, the social economy furthers stakeholder engagement and improves social acceptance of circular products and green technologies, and it promotes more circular and sustainable behaviors (OECD/European Commission, 2022).…”
Section: Introductionmentioning
confidence: 99%